Epicuro: sabedoria e finitude - Maffisoni, Marcos Antonio (2017)
This work presents an interpretation of Epicurus’ philosophy from the way of life that Epicurean assumes, the major mark of the doctrine. Given that the uniqueness of a project of wisdom is its fundamental characteristic, the whole theoretical contribution of the epicurean doctrine was presented considering its reasons and its practical purposes. Thus, in order to appropriately comprehend and expose this way of life, it was sought to deal with the theoretical bases that support the thought of Epicurus and which represent the attempt to understand the human nature in its material and sensible reality, from the presuppositions of the physics and the canon, predominantly accentuating its existential and moral consequences and conclusions. In this way, from the atomism which Epicurus assumes, it was emphasized the thesis of the mortality of the soul and the derivative idea of finitude, fundamental to understand the epicurean way of life in its intention to pleasantly live the present. It was also reflected, from the postulates of the canon, how Epicurus comes to enounce the pleasure as the ultimate reference of human nature and, mainly, it was contemplated the epicurean hedonism, which intended not only pleasures but a pleasant life. In sequence, it was considered the epicurean ethic in a way to highlight, at first, the grateful disposition that the Epicurean assumes in relation to life. In consequence, it was analyzed the wisdom project development starting from the considerations about the desires and the exercise of the phronesis At last, it was approached the partial removal of the Epicurean from the polis, justified by the renunciation of the ideals of power, recognition and wealth; and this work was concluded with the ultimate characterization of the way of life proposed by Epicurus: the possession of friendship, which is, at the same time, the crowning of ethics and the experience that makes Epicureanism, more than a system of thought, a lived wisdom that becomes a movement.